Clinical Use of Short-Course and Low-Dose Corticosteroids in Patients With Non-severe COVID-19 During Pneumonia Progression - Hu, Zhiliang; Lv, Yanling; Xu, Chuanjun; Sun, Wenkui; Chen, Wei; Peng, Zhihang; Chen, Chen; Cui, Xiang; Jiao, Damin; Cheng, Cong; Chi, Yun; Wei, Hongxia; et al. (Frontiers in Public Health, 2020)
Background: The emerging coronavirus disease 2019 (COVID-19) has become a serious public health concern with a high number of fatalities. It is unclear whether corticosteroids could be a candidate for an early intervention strategy for patients with COVID-19. Methods: In this retrospective cohort study, we analyzed data from 28 corticosteroid-treated patients with non-severe but advanced COVID-19, in which short-course and low-dose corticosteroids were administered because of unremitting or worsening clinical conditions during hospitalization. To compare the effect of corticosteroids on viral clearance, 44 corticosteroid-untreated patients were included as controls. Results: At the time of admission, corticosteroid-treated patients (n = 28) had a more advanced baseline illness compared with corticosteroid-untreated patients (n = 44), as reflected by poorer blood laboratory parameters (lymphocytes, C-reactive protein, and lactate dehydrogenase) and more extensive chest computed tomography (CT) abnormalities. Corticosteroids were given because of radiological evidence of pneumonia progression (26/28) and/or unremitting fever (22/28) after admission. The median time from illness onset to corticosteroid treatment was 9 days (IQR, 7–10). The median duration and accumulated dose of corticosteroid treatment were 4.5 days [interquartile range (IQR), 3–5] and 140 mg of methylprednisolone (IQR, 120–200). Intravenous immunoglobulin (20 g per day for 3–5 days) was co-administered with corticosteroids. With the corticosteroid treatment, all patients achieved an abatement of fever within 1 day, and 78.6% (22/28) of the patients achieved radiological remission when evaluated about 3 days later. Only one (3.6%) patient progressed to severe COVID-19, and all patients recovered and were discharged without any sequela. The median time from illness onset to viral clearance was similar, as compared with 44 corticosteroid-untreated patients with relatively milder disease [18 (IQR 14.3–23.5) days vs. 17 (IQR, 12–20) days, p = 0.252]. When adjusted for age, sex, underlying comorbidities, baseline blood laboratory parameters, viral load, and chest radiological findings, the causal hazard ratio of corticosteroid treatment for the viral clearance was 0.79 (95%CI, 0.48–1.30, p = 0.34). Conclusion: Short-course and low-dose applications of corticosteroids, when co-administered with intravenous immunoglobulin, in non-severe COVID-19 patients during the stage of clinical deterioration may possibly prevent disease progression, while having a negligible impact on the viral clearance.